PARTISIPASI DAN KOMUNIKASI POLITIK PEREMPUAN DI LEGISLATIF MENURUT KACAMATA POLITISI PEREMPUAN DI INDONESIA - Parwati, Theresia; Istiningdiah, Kuspuji (Interaksi: Jurnal Ilmu Komunikasi, 2020)
Today, women political participation is still low in number. It causes the shortness of women representation in policy and decision making. In fact, the representation of women has not been heard fully in the public space. Many women's voices have not been conveyed. This article examined woman’s political participation and communication in the political area in Indonesia. The main problems of this research were why the participation of women in politics in formal institutions relatively low and how the communication role in that matter. This research used descriptive qualitative method by interviewing 18 women politicians in legislative on June 26th until July 4th online. The research findings show the lack of women participation as the representative. The low representation of women in direct political participation was influenced by various internal and external factors. They included women’s unwillingness to plunge directly into the world of practical politics, patriarchy cultural factors, and incapability of women to solve lots of real-problems. It is why we still need the right step to create equality and access to women in the political scope.